The Attitudes and Awareness of Urinary Bladder Cancer Patients about the Relationship Between Their Tumoral Diseases and Tobacco Exposure - ÖZDİLEKCAN, Çiğdem; GÜVEN, Eşref Oğuz; GÜVENİR, Fahrettin; KARAİSMAİLOĞLU, Eda (Cagdas Tip Dergisi: Journal of Contemporary Medicine, 2020)
Aim: To investigate the urinary bladder cancer (UBC) patients about their smoking behaviors and to find out the answer for their attitudes and awareness of the exposure cancer relationship. Material and methods: A cross- sectional study was conducted between January 2018- December 2019. Results: One hundred seventy- nine histopathologically proven UBC patients were included . The majority of patients (57.1%) attempt to quit smoking before diagnosis. 42.9 %of them quitted during diagnostic procedures or after being diagnosed as cancer. No significant relationship was found between the smoking status and recurrence of the primary tumoral disease. The grade of the primary tumor and chemotherapy applications did not affect the smoking status of the patients (p=0.521 and p=0.949 respectively). When the awareness about their smoking behavior which was one of the major causes for their bladder cancer was asked; 60 % of the participants were absolutely not aware. When the main reason for smoking cessation was asked, the positive influence and strong advice of healthcare professionals for quit smoking were the most important factor for the patients. However, either gradually worsening quality of life or suffering from serious respiratory illnesses (COPD, asthma ) were not the major factors to quit smoking. Conclusions: Majority of the patients didn’t have any or particularly had idea about the relationship between smoking and urothelial cancers. Among the patients who had harm perception of smoking on their tumoral diseases, majority didn’t believe that quitting would be beneficial after being diagnosed as cancer. Key words: Awareness ,knowledge , urinary bladder cancer,tobacco smoking
Keywords: knowledge; urinary bladder cancer; Awareness; knowledge; urinary bladder cancer; Farkındalık; bilgi; mesane kanseri; tütün içimi; mesane kanseri; R; Sağlık Kurumları Yönetimi; Health Care Administration; Medicine; awareness; bilgi; tütün içimi; farkındalık; 3. Good health